Labors of Love and Loss: Radical Acts of Human, Plant, and Nonhuman Mothering - Dare, Alexa; Fletcher, Vail (Journal of Ecohumanism, 2023)
As we begin to pick up the scattered pieces of our lives upended by a global pandemic, there is still little clarity about what comes next; and yet it has been laid perfectly bare that mothering is both essential and chronically undervalued. For the two editors of this special issue, we are among millions who are raising kin (human and nonhuman alike) in the Anthropocene. Who both worry desperately for what the future will look like, and who practice love and care in the face of crisis, extinction, contamination, aggression, and more. We are interested in taking seriously mothering and other forms of caregiving as radical acts of ecosurvival, and so we invited human animal collaborators to this special issue to help us collectively think through the ways in which love, intimacy, mothering, caregiving, and/or kinmaking are practices of resistance, solidarity, or world-making. The response to our invitation – in both scope and depth – was immense. Scholars and poets and artists everywhere have already been imagining – and witnessing – a new world being born and broadened to allow new stories of survival and kinship to take hold.